Analysis of Effect on Service Recovery Four Star Hotel in Semarang City - Heridiansyah, Jefri; Susetyarsi, Theresia; Indriastuti, Ariyani; Triasningrum, Frida Widyawati (Universitas Negeri Semarang, 2020)
The purpose of this study is to find out: (1) How much influence does customer satisfaction have on the four-star hotel service recovery in Semarang City. (2) How much impact of customer trust on the service recovery of four-star hotels in Semarang, (3) How big is the influence of customer commitment on service recovery for four-star hotels in Semarang City. The sample in this study amounted to 57 respondents or customers. This study was analyzed using multiple linear regression includes the T-test, F test, and the coefficient of determination. Based on the results of the research and discussions, it can conclude that there is an effect of customer satisfaction on service recovery, there is an effect of customer trust on service recovery also there is an effect of customer commitment on service recovery.